2017
DOI: 10.1080/16549716.2017.1289736
|View full text |Cite
|
Sign up to set email alerts
|

Survey of ENT services in sub-Saharan Africa: little progress between 2009 and 2015

Abstract: Background: A 2009 survey of ENT, audiology, and speech therapy services and training opportunities in 18 Sub-Saharan African countries reported that the availability of services was extremely poor, the distribution of services was very inequitable, and training opportunities were limited.​​Objective: We conducted a new survey to determine the current status of ear, nose, and throat (ENT), audiology, and speech therapy services in sub-Saharan Africa.Method: This study is a cross-sectional study. A questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
177
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(183 citation statements)
references
References 13 publications
5
177
0
1
Order By: Relevance
“…The concept of CHW‐driven screening using mobile technology has been successfully employed in ophthalmology, dermatology, and orthopedics . CHWs are generally available and can act as an intermediary between children in rural settings and the advanced healthcare personnel (such as audiologists and otolaryngologists) that are otherwise scarce in LMICs . Using these intermediaries allows for the scalability of these programs as their initial screening process allows for selective referrals, thereby reducing the burden upon the more scarce specialized hearing healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of CHW‐driven screening using mobile technology has been successfully employed in ophthalmology, dermatology, and orthopedics . CHWs are generally available and can act as an intermediary between children in rural settings and the advanced healthcare personnel (such as audiologists and otolaryngologists) that are otherwise scarce in LMICs . Using these intermediaries allows for the scalability of these programs as their initial screening process allows for selective referrals, thereby reducing the burden upon the more scarce specialized hearing healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given the substantial number of people with hearing loss, without good access to ear and hearing services, UHC will not be achieved. Evidence suggests that the current level of access to hearing specific services is inadequate in LMICs [19,20]. A recent systematic review of access to rehabilitation for people with disabilities found that coverage of assistive devices for people with hearing loss was unacceptably low across LMICs where data existed, ranging from 0 to 24% at the population-level [21].…”
Section: Introductionmentioning
confidence: 99%
“…While applicable worldwide, using a mobile platform could potentially address the mostly nonexistent access to hearing screening in low-and-middle income countries. In sub-Saharan Africa, for instance, there is only one audiologist for every million people (Mulwafu et al 2017). As a result, the South African English DIN was developed and released as the national hearing screening application in 2016, downloadable on iOS and Android smartphones, called hearZA TM (Potgieter et al 2016;De Sousa et al 2018).…”
Section: Introductionmentioning
confidence: 99%